Coping and motivational strategies of non-elite endurance athletes under extreme environmental conditions – a salutogenic perspective - Steyn, Barend Johannes Marthinus (University of Pretoria, 2013)
Thesis (DPhil (Human Movement Science))--University of Pretoria, 2007.